Criminal Liability for Environmental Pollution by the Corporate - Santosa, Muhari Agus (2017)
Research on criminal accountability of environmental pollution which is committed by a corporation shows on multinational corporations have shown a massive accumulation of wealth, and creating a wide gap between personal. There is a very rich and still very much the poor. Even large corporations that dominate the world economic system, and can specify the job for many people, the food, drink and clothing, and so forth. Corporations can also threaten the government of a country in which the corporation operates. Whereas in the field of criminal law, which relates to the weight of this responsibility referred to in the draft Criminal Law (Penal Code) only recognize the individual as a subject of criminal law. For the corporation has not been regarded as a subject of criminal law. However, in the subsequent development mentioned in the special criminal law. Relationship with vicarious liability or responsibility of corporations in criminal law can be described as the imposition of criminal responsibility to a person in the capacity of the main actors, based on the act violation or at least there is an element of violations committed by others. Those who do, however, must take responsibility for his actions limited. It required firmness to lay criminal responsibility on offense corporate environment so that corporations that make careless exploit aolam that cause pollution can be imprisoned according degan mistakes. Similarly, it takes socialized to maskarayat about the possibility of environmental offenses that should be accounted for by the corporation. It is thus essential to solicit public participation in maintaining environmental wisdom. Keywords: Criminal accountability, Environmental Pollution, Corporatio